Movement and survival of captive-bred Limosa harlequin frogs (Atelopus limosus) released into the wild - Klocke, Blake; Estrada, Angie; Mataya, Mirjana; Medina, Daniel; Baitchman, Eric; Belden, Lisa; Guerrel, Jorge; Evans, Matthew; Baughman, Jeff; Connette, Grant; Illueca, Estefany; Ibáñez, Roberto; et al. (Frontiers in Amphibian and Reptile Science, 2023)
The endangered Limosa harlequin frog Atelopus limosus has experienced significant chytridiomycosis-related declines, but has been successfully bred in captivity as part of the Panama Amphibian Rescue and Conservation Project. We conducted the first Atelopus release trial using 83 captive-bred A. limosus, and monitored individuals as they transitioned from captivity back into the wild at a site within their historic distribution with no extant population. We acclimated 23 animals to the environment prior to release by holding them in mesocosms for 30 days (soft release) and released a further 60 animals without prior acclimation (hard release). We radio-tracked a subsample of animals in each treatment group. We used a Bayesian mark–recapture analysis to integrate known fate data from radio-tracked individuals with data from resighted individuals that had unknown fates. For this analysis, we allowed survival to differ between release treatments (hard vs. soft) and assumed detection probability would differ between tracking methods. Per-survey detection probability was about 0.02 for individuals without radio transmitters vs. 0.88 for radio-tracked frogs. We observed that hard-released animals initially dispersed further than soft-released animals, and, despite the fact that 25% of the soft-released animals were Batrachochytrium dendrobatidis (Bd)-positive on release day, their estimated 30-day survival probability was 0.46 (vs. 0.31 for the hard-released animals). The insights from this release trial can be used in an adaptive management framework to improve and refine release methods that will inform the nascent field of amphibian reintroduction ecology.